Control of the private security sector in foreign countries - Stajić, Ljubomir (Zbornik radova Pravnog fakulteta u Novom Sadu, 2012)
All modern states today have organized and regulated system of security that includes different role of private security sector which is defined and limited by law. The law respresents the basis and limits the activities of all social subjects including the private security sector. Today, legal regulation of private security industry has gone very far in modern democratic societies. So-called model of control through the contract with the bussiness model is abandoned and approach to the model of control by the state is accepted. The new model has almost the same elements used by the state when it comes to controling the public sector or the police. Analyses indicate that issues related to the control of the private security can be legally regulated in a manner that is typically European, but also have an entirely different approach and variety of combinations that regulate the functioning of private security sector respecting national characteristics. The paper represents the main principles of control of private security abroad with special emphasis on the possible role of international law.
Keywords: protection of property and business; control; private security; security